Exogenous IFN-gamma ex vivo shapes the alloreactive T-cell repertoire by inhibition of Th17 responses and generation of functional Foxp3+ regulatory T cells. - Feng, G; Gao, W; Strom, T; Oukka, M; Francis, R; Wood, K; Bushell, A (2008)
Interferon (IFN)-gamma was originally characterized as a pro-inflammatory cytokine with T helper type 1-inducing activity, but subsequent work has demonstrated that mice deficient in IFN-gamma or IFN-gamma receptor show exacerbated inflammatory responses and accelerated allograft rejection, suggesting that IFN-gamma also has important immunoregulatory functions. Here, we demonstrate that ex vivo IFN-gamma conditioning of CD4 T cells driven by allogeneic immature dendritic cells (DC) results in the emergence of a Foxp3(+) regulatory T-cell (Treg)- dominant population that can prevent allograft rejection. The development of this population involves conversion of non-Treg precursors, preferential induction of activation-induced cell death within the non-Treg population and suppression of Th2 and Th17 responses. The suppressive activity of IFN-gamma is dependent on the transcription factor signal transducer and activator of transcription 1 and is mediated by induced nitric oxide. These data indicate not only how IFN-gamma could be used to shape beneficial immune responses ex vivo for possible cell therapy but also provide some mechanistic insights that may be relevant to exacerbated inflammatory responses noted in several autoimmune and transplant models with IFN-gamma deficiency.